An Improved Method for Development of Seed Production Areas of Chir Pine - Gera, Mohit (Indian Forester, 2002)
Tree improvement is effected through a series of operations leading to genetic upgrading of the species. Development of Seed Production Areas (SPAs) is the first level of genetic improvement and ensures to fulfil interim seed requirement. SPAs have been selected on the basis of ocular judgement in the past. An improved method of scoring has been introduced recently by F.R.I. which is said to overlook certain unimportant features such as elimination of deceased, forked, over-mature trees. A combination of these two methods, i.e., ocular judgement and scoring is being applied in marking of seed stands and individual trees in case of Chir pine in J & K State. The new method sounds robust, is user friendly and takes care of shortcomings of the earlier procedures and has been sescribed in detail in this article.